(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to seek important causal factors, volume of predictions and orders of predictors in psychological traits group, situations group and psychological states group regarding fellowship behavior of youth in the community. This study examined comparative relation based on fundamental concepts of the interactionism theory. The samples included 480 youth who were randomly selected with multi-stage and quota sampling method. Multiple regression analysis of enter and stepwise formats and three-way analysis of variance were applied for analyzing data in main group and 6 sub-groups. The findings revealed that 10 independent variables could predict fellowship behavior 1) in main group for 40.40 % with key predictors of Need for Achievement, Social Norms, Mental Health and Good Attitude towards Good Citizenship Behavior in Democratic Way with beta valued at 0, .14,-.1 , and .1, respectively, and ) could predict the sub-groups varied from 6.0-4.0% with highest predictability at 1.0 % among male youth in the community. The study result indicated guidelines of essential research and development in order to strengthen the youth to have appropriate behaviors of fellowship.